Anemia and Associated Factors Among Lactating Women in Sierra Leone: An Analysis of the Sierra Leone Demographic and Health Survey 2019 - Arinda, Ivan Kato; Sserwanja, Quraish; Kamara, Kassim; Mukunya, David; Napyo, Agnes; Nsubuga, Edirisa Juniour; Nuwahereza, Christinah; Kagali, Anitah; Seungwon, Lee (Nutrition and Metabolic Insights, 2019)
Anemia is a condition in which hemoglobin (Hb) concentration and/or red blood cell (RBC) numbers are lower than normal and insufficient to meet an individual’s physiological needs. The prevalence of anemia among women of reproductive age is high in Sub-Saharan Africa (SSA), including Sierra Leone. However, data on anemia among lactating women in Sierra Leone are scarce. Therefore, this study was conducted to estimate the prevalence of anemia and determine its associated factors among lactating women in Sierra Leone.The 2019 Sierra Leone Demographic and Health Survey (SLDH) data were used of which 1543 lactating women aged 15 to 49 years old had hemoglobin measurements. Multistage stratified sampling was used to select study participants and data were collected using validated questionnaires. Multivariate binary logistic regression was used to determine factors associated with anemia among lactating women in Sierra Leone.The general prevalence of anemia among lactating women in Sierra Leone was 52.9% (95% CI = 50.9-55.8). Almost a quarter, 23.8% (95% CI = 22.1-26.3) of the lactating women had mild anemia, 27.4% (95% CI = 25.3-29.7) had moderate anemia and 1.7% (95% CI = 1.1-2.5) had severe anemia. The use of modern contraceptives (aOR = 1.64, 95% CI = 1.09-2.47), not being visited by a field worker in the past year (aOR = 1.51, 95% CI = 1.12-2.03) and being Muslim (aOR = 1.46, 95% CI = 1.11-1.91), were associated with higher odds of being anemic. Being given and having bought iron supplements during pregnancy (aOR = 0.46, 95% CI = 0.25-0.87) was associated with less odds of being anemic.More than half of the lactating mothers in our study were anemic. The risk factors for anemia in our study included: use of modern contraceptives, not being visited by a field worker in the past year and being Muslim. Receiving iron supplements during pregnancy was protective against anemia. According to the results from this study, the recommendation for lactating women was to maintain routine interface with the healthcare system which includes being visited by a field worker who should prescribe and issue iron supplements to them. Lactating women especially Muslims should receive routine nutrition education by the health workers at the health facilities during antenatal care visits or postnatal care in regard to anemia and means of prevention and treatment. Community stakeholders should also work in collaboration to establish scalable methods to correctly identify pregnant women with risk factors, inform them about anemia with caution, and apply appropriate measures as trained or instructed
Keywords: Anemia, lactating women and Sierra Leone